2011
DOI: 10.1111/j.1755-5922.2011.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a New Accelerated Streptokinase Regime in Acute Myocardial Infarction: A Double Blind Randomized Clinical Trial

Abstract: SUMMARYBackground: Studies of thrombolysis in acute ST-elevation myocardial infarction (STEMI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
1
8
1
3
Order By: Relevance
“…Mean pre-discharge EF was significantly higher in patients receiving accelerated SK regimen when compared to those who received traditional regimen (50.9 ± 6.6% versus 47.3 ± 4.6% respectively, P  = 0.002), a result that is closely similar to that reported by Ghaffari et al 11 …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Mean pre-discharge EF was significantly higher in patients receiving accelerated SK regimen when compared to those who received traditional regimen (50.9 ± 6.6% versus 47.3 ± 4.6% respectively, P  = 0.002), a result that is closely similar to that reported by Ghaffari et al 11 …”
Section: Discussionsupporting
confidence: 87%
“…Ghaffari et al 11 performed a randomized double-blind clinical trial comparing an accelerated infusion (1.5 MU/20 min) with the conventional infusion (1.5 MU/60 min) of SK in 300 patients with their first episode of acute STEMI. In multivariate analysis, accelerated SK infusion was the only independent predictor of higher coronary reperfusion (OR = 3.2, CI: 1.93-5.3, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…TLT-related complications were recorded for each patient. Previously, we showed that transient hypotension during streptokinase infusion is readily corrected by concomitant rapid saline infusion in almost all patients [16], so, we did not consider this reaction as a complication during the present study. Other concomitant therapies were permitted at the discretion of the managing physician.…”
Section: Tlt Regimenmentioning
confidence: 85%
“…The efficacy and safety of this regimen has been previously shown [16]. Additionally, they received acetyl salicylic acid 300 mg, clopidogrel 300 mg to 600 mg orally, unfractionated or low molecular weight heparin, and statins.…”
Section: Thrombolytic Treatmentmentioning
confidence: 99%